Biodegradable plastic production based on cassava starch through a thermomechanical process - Jiménez Villalta, Guillermo Alfonso (2024)
The present research aims to formulate a thermoplastic polymer based on starch (TPS) extracted from a cassava variety, through a thermomechanical processing in an internal mixer. Three formulations, guided by preliminary tests, were analyzed to choose a base formulation. Polyvinyl alcohol (PVOH) was chosen to reinforce TPS. Likewise, a statistical study of the processing conditions was carried out, from which the temperature was optimized at 110 °C, the rotor speed at 75 rpm (1,25 Hz), and the processing time at 6 min. Finally, through adjustment of the relative percentages of the components, a material with a tensile stress of 15,4 ± 0,9 MPa and a strain deformation of 44 ± 11 % was achieved. An aging test showed that properties of the TPS materials reached stabilization after 15 days of their formation. In the same way, a biodegradability test showed a reduction in the plastic mass of 98,5 ± 0,3 % after 22 days of being buried. Under controlled conditions, the material exhibits adequate mechanical properties for use in everyday applications; however, it is necessary to address its sensitivity to ambient humidity, as this significantly influences these mechanical properties.